2016
DOI: 10.1111/trf.13912
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative blood transfusion: does it influence survival and cancer progression in metastatic spine tumor surgery?

Abstract: This is the first study providing evidence that disease progression and survival in patients who undergo MSTS are less likely to be influenced by perioperative ABT. The worst oncologic outcomes are more likely to be caused by the clinical circumstances necessitating blood transfusion, but not transfusion itself. However, because ABT can have a propensity toward developing postoperative infections, including surgical site infection, the use of patient blood management interventions would be worthwhile rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
1
13
0
1
Order By: Relevance
“…Our results revealed that patients with multiple spinal metastases did not have a significantly shorter survival time compared to patients with solitary spinal metastasis, which is completely opposite from certain existing literature and scoring systems 8, 9 and 11. The obtained findings are in accordance with previous reports from the literature: Yang et al . found that the median survival for patients with SSM was 7 months, while it was 5 months for patients with MSM.…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that patients with multiple spinal metastases did not have a significantly shorter survival time compared to patients with solitary spinal metastasis, which is completely opposite from certain existing literature and scoring systems 8, 9 and 11. The obtained findings are in accordance with previous reports from the literature: Yang et al . found that the median survival for patients with SSM was 7 months, while it was 5 months for patients with MSM.…”
Section: Discussionsupporting
confidence: 93%
“…The patients were categorized into different subgroups based on primary tumor type, type of surgical approaches, levels of instrumentation, and decompression as in our previous studies in MSTS. 21,25,26 Categorical variables are presented as numbers with percentages and continuous variables as mean 6 SD as per the distribution of data. Fisher's exact test was used for comparing categorical variables and t test was used for continuous variables.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses were performed using statistical software (STATA, Release 13.0, StataCorp). The patients were categorized into different subgroups based on primary tumor type, type of surgical approaches, levels of instrumentation, and decompression as in our previous studies in MSTS …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Je seltener ein einzelnes Ereignis ist, desto schwieriger ist es, dies auch in großen Studien oder Metaanalysen zu erfassen. [52,53], während andere keinen Zusammenhang zeigen [54,55] (▶ Tab. 1).…”
Section: Kurzfristige Und Langfristige Immunologische Auswirkungen Vounclassified